2015
DOI: 10.1007/s12560-015-9193-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Molecular Characterization of Hepatitis E virus in Domestic Animals and Wildlife in Croatia

Abstract: Hepatitis E is becoming a growing health concern in European countries as an increase of sporadic human cases of unknown origin has been recorded lately. Its causative agent, Hepatitis E virus (HEV), is known to have zoonotic potential and thus the role of domestic and wild animals in the chain of viral spread should be considered when investigating risk factors and the epidemiology of the disease. A comprehensive survey based on viral RNA detection was carried out in Croatia including blood, spleen and liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 44 publications
(56 reference statements)
11
37
0
Order By: Relevance
“…Both results correspond to results previously reported in European countries (BURRI et al, 2014;ANITA et al, 2014;MONTAGNARO et al, 2015;THIRY et al, 2015;MAZZEI et al, 2015). The majority of samples tested within our study were collected from the northern regions of Croatia, where heV rNa prevalence in pigs and wild boars L. Jemeršić et al: Hepatitis E virus persistence in pigs and wild boars in Croatia was previously detected (PRPIĆ et al, 2015). Our study reveals a statistically significant (P<0.0001) higher seroprevalence detected in domestic pigs and wild boars from OsijekBaranja and Vukovar-Srijem Counties than from all other counties included in the study.…”
Section: Serology Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Both results correspond to results previously reported in European countries (BURRI et al, 2014;ANITA et al, 2014;MONTAGNARO et al, 2015;THIRY et al, 2015;MAZZEI et al, 2015). The majority of samples tested within our study were collected from the northern regions of Croatia, where heV rNa prevalence in pigs and wild boars L. Jemeršić et al: Hepatitis E virus persistence in pigs and wild boars in Croatia was previously detected (PRPIĆ et al, 2015). Our study reveals a statistically significant (P<0.0001) higher seroprevalence detected in domestic pigs and wild boars from OsijekBaranja and Vukovar-Srijem Counties than from all other counties included in the study.…”
Section: Serology Resultssupporting
confidence: 92%
“…all isolates belonged to genotype heV-3 (PRPIĆ et al, 2015). In our present study we supplemented the epidemiological data with the first results of HEV seroprevalence in domestic pigs and wild boars from 14 and 16 counties in Croatia (table 1), respectively.…”
Section: Serology Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The highest seroprevalence of 70.6% and the lowest seroprevalence of 12.1% were noted in Italy, in sows and weaners, respectively (Mazzei et al 2015b). In contrast, a study in Croatia reported the highest prevalence of HEV in the age class of 1-4 week suckling piglets (Prpic et al 2015). Our study results support the notion by Pavio et al (2010) that wide variations in within-herd seroprevalence would appear to be the norm in HEV-infected herds.…”
Section: Discussionsupporting
confidence: 77%
“…A Polish study determined 44.4% of HEV antibodies in the serum of wild boar from 11 different Polish provinces (Larska et al 2015), while a Spanish study found an overall seroprevalence of 42.7% in wild boar population from South Central Spain, whereas IgG seroprevalence ranged from 0% to 63.3% depending on geographical region. On the other hand, overall seroprevalence in wild boar population in Switzerland and Croatia was reported to be 12.5% (Burri et al 2014) and 12.3% (Prpic et al 2015) of all tested samples, respectively.…”
Section: Discussionmentioning
confidence: 90%